2005
DOI: 10.1016/j.micromeso.2005.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Solvent effects in the synthesis of CoAPO-5, -11 and -34 molecular sieves

Abstract: Series of CoAPO-5, CoAPO-11 and CoAPO-34 molecular sieves have been synthesized starting from a synthesis gel varying in its amount of Co 2+ and type of solvent molecule. Four protonic solvents have been investigated: water, ethanol, ethylene glycol and glycerol. The obtained crystalline materials were characterized with X-ray diffraction; diffuse reflectance UV-Vis-NIR spectroscopy; infrared spectroscopy; elemental analysis; electron microscopy microprobe analysis and thermo-gravimetrical analysis. It was fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…We note that the role of both the template molecule and the solvent is not considered in this model. However, since many different templates and a variety of solvents (both protic and aprotic) have been used to synthesize AFI and since the same template can be used to crystallize different aluminophosphate structures, we surmise that their role is not specific for AFI crystallization and therefore the mechanism proposed can be considered to be generally applicable. , The Co 2+ ions influence the crystallization process by hindering and therefore retarding it. It is most likely that this is related to the necessity of the Co 2+ ions to transform from octahedral into a tetrahedral geometry before being incorporated into the Al−O−P network.…”
Section: Discussionmentioning
confidence: 95%
“…We note that the role of both the template molecule and the solvent is not considered in this model. However, since many different templates and a variety of solvents (both protic and aprotic) have been used to synthesize AFI and since the same template can be used to crystallize different aluminophosphate structures, we surmise that their role is not specific for AFI crystallization and therefore the mechanism proposed can be considered to be generally applicable. , The Co 2+ ions influence the crystallization process by hindering and therefore retarding it. It is most likely that this is related to the necessity of the Co 2+ ions to transform from octahedral into a tetrahedral geometry before being incorporated into the Al−O−P network.…”
Section: Discussionmentioning
confidence: 95%
“…Despite of this, it was found that all reflections in the XRD patterns of Co-containing samples shifted to lower positions, as compared to the materials free of this element. This reveals that addition of Co in the synthesis gel led to an enlargement of the unit-cell volume as a result of the unit-cell expansion [8][9][10][11], showing that Co 2+ ions were easily incorporated in the framework. This is further confirmed by the data shown in Table 1.…”
Section: Catalyst Synthesis and Characterizationmentioning
confidence: 89%
“…A divalent Co(II) cation may be accommodated in SAPOs either on a substitutional site (replacing a trivalent Al ion) and forming a Broensted acid site after protonation or as an extraframework cation forming a Lewis site . The ratio of substitutional and extraframework Co(II) depends strongly on the preparation conditions.…”
Section: Ab Initio-optimized Crystalline Geometriesmentioning
confidence: 99%